The Main Characteristics of English Legal Language - Sanja Gavrilovska (University "St. Kliment Ohridski" - Bitola, Faculty of Education - Bitola, Macedonia, 2016)
The aim of this paper is to describe the development of English legal language through history and to present its most salient features. First of all the influence of the Anglo-Saxons on this type of language , then the influence of Christian missioneries in 597 A.D. who introduced many Latin terms in English legal language and the Norman invasion in 1066 A.D. which made the French language an official language in England. French, Latin and English were used simultaneously up to 1730 when English became the only official language of English legal system. The language of the law is a specific type of language which consists of one part which is general language code and another part which is normative legal language. It differs from general English in several segments: a) legal language contains long, complex sentences, b) English legal language uses terms which are unknown to non-professionals, c) there are words from general language which have special meaning in law, d) impersonal and passive constructions and nominalisations are characteristic for legal language, e) legal acts are written in an unemotional, unexpressive and rational language, g) the modal verb “shall” has an uncommon usage in legal language etc. English legal language is a separate part of general English with its own lexical, semantic and syntactic features and it is a part of the ESP (English for Specific Purposes) language family.
Specialized paper
Keywords: English legal language, general English, complex sentences, passive constructions, nominalizations, English for Specific purposes